2022
DOI: 10.1371/journal.pone.0266401
|View full text |Cite
|
Sign up to set email alerts
|

Co-creative art processes with patients: A theoretical framework and qualitative study among artists

Abstract: A cancer diagnosis may be experienced as a contingent life event. Co-creation—in which artists together with patients create a work of art reflecting on aspects of the patients’ life story—may be used to support patients to integrate such a contingent life event into their life story. We conducted a qualitative study in which we interviewed 10 professional artists to explore if co-creative art processes could facilitate integration of experiences of contingency in patients. Template analyses were performed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(31 citation statements)
references
References 19 publications
2
29
0
Order By: Relevance
“…In previous research, 13 we found that the integration of experiences of contingency showed resemblances with resonance theory, as described by Rosa 17–19 . Resonance theory and contingency have previously been used as a theoretical framework in research on cancer patients, investigating a process of observing art works to create new meaning 20 .…”
Section: Introductionsupporting
confidence: 68%
See 4 more Smart Citations
“…In previous research, 13 we found that the integration of experiences of contingency showed resemblances with resonance theory, as described by Rosa 17–19 . Resonance theory and contingency have previously been used as a theoretical framework in research on cancer patients, investigating a process of observing art works to create new meaning 20 .…”
Section: Introductionsupporting
confidence: 68%
“…Palliative cancer patients participated in the ISOS project, which is a narrative multimodal intervention aimed at enhancing quality of life 11,13,14 . ISOS is a joint project of the Department of Medical Oncology of Amsterdam University Medical Centres in collaboration with the Faculty of Philosophy, Theology and Religious Studies of the Radboud University, Nijmegen, the University of the Arts Utrecht and Amsta Healthcare Organisation Amsterdam.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations